Applying the Unified Theory of Acceptance and Use of Technology (UTAUT) to Analyze Use Behavior of the Quick Response Code Indonesian Standard (QRIS) Among Generation Z in Bandung - Angger Cakra Wibisono; Novi Susyani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the factors influencing the use behavior of Generation Z in using the Quick Response Code Indonesian Standard (QRIS) in Bandung by applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model. A quantitative approach with descriptive and associative research design was employed, using primary data collected through an online questionnaire distributed to 100 Generation Z respondents who actively use QRIS. The research variables consisted of performance expectancy, effort expectancy, social influence, and facilitating conditions as independent variables, and use behavior as the dependent variable. Data were analyzed using multiple linear regression with the support of SPSS, accompanied by validity, reliability, and classical assumption tests. The results indicate that all independent variables simultaneously have a significant effect on use behavior. Partially, performance expectancy, effort expectancy, social influence, and facilitating conditions each show a positive and significant influence on QRIS use behavior, with social influence identified as the most dominant factor. This study concludes that the UTAUT model effectively explains QRIS use behavior among Generation Z in Bandung, where perceived usefulness, ease of use, social influence, and supporting facilities play a crucial role in encouraging sustainable QRIS usage.